Regulatory T cells and their potential for tolerance induction in haemophilia A patients - Schmidt, A.; Königs, C.; ABIRISK consortium; on behalf of (Hämostaseologie, 2016)
FVIII inhibitors still are the major concern in treatment of haemophilia A patients by FVIII replacement therapy. Immune tolerance induction to reverse inhibitor formation fails in about 30% of treated patients. These patients face increased morbidity and mortality producing a need for new therapy strategies in the treatment of FVIII inhibitor-positive patients. Regulatory T cells are important modulators of the immune response and are also involved in the immune response to FVIII in haemophilia A patients. Additionally, regulatory T cells have been shown to play a role in tolerance induction induced by multiple experimental treatment regimes.This review summarises the current knowledge on the role of regulatory T cells in the immune response to FVIII and tolerance induction strategies. Additionally, possible ways to engineer regulatory T cells as therapeutic agent in haemophilia A and current challenges of regulatory T cell therapies are discussed.
Keywords: Häemophilia A; tolerance; regulatory T cells